Register variation online - Biber, Douglas 1952-; Egbert, Jesse 1985- (Cambridge University Press, 2018)
While other books focus on special internet registers, like tweets or texting, no previous study describes the full range of everyday registers found on the searchable web. These are the documents that readers encounter every time they do a Google search, from registers like news reports, product reviews, travel blogs, discussion forums, FAQs, etc. Based on analysis of a large, near-random corpus of web documents, this monograph provides comprehensive situational, lexical, and grammatical descriptions of those registers. Beginning with a coding of each document in the corpus, the description identifies the registers that are especially common on the searchable web versus those that are less commonly found. Multi-dimensional analysis is used to describe the overall patterns of linguistic variation among web registers, while the second half of the book provides an in-depth description of each individual register, including analyses of situational contexts and communicative purposes, together with the typical lexical and grammatical characteristics associated with those contexts